Zinc requirement of soybean (Glycine max) - wheat (Triticum aestivum) cropping sequence in some swell-shrink soils - BARMAN, K K; GANESHAMURTHY, A N; TAKKAR, P N (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted on 6 swell-shrink soils through laboratory and green-house experiment on zinc requirement of soy be all (Glycine max L.) -wheat (Triticlim aestivum L. emend. Fiori & Paol.) cropping sequence. From the incubation study, mathematical relationship between added zinc and built-up soil zinc was worked out. Soil DTPA-Zn levels were built up to 0.5, 1.0, 1.5, 2.0, 3.0 and 6.0 ppm by adding desirable amount of zinc through ZnSO4.7H2 O. Soybean and wheat were grown in rotation in these treated soils. Results indicated that 21.5 to 33% of the added zinc contributed towards the pool of DTPA-Zn in soils. Optimum dry matter yield of soybean was obtained at the built up DTP A -Zn level of 1.0 ppm in all the soils. The initial build up DTPA-Zn also showed significant residual effect on the following wheat crop. The DTPA-Zn contents of 1.1 to 1.2 ppm were found to be adequate for the optimum wheat dry matter production in these soils. It was concluded that the zinc requirement of soybean -wheat cropping sequence could be met by building up the DTPA-Zn content of the soils to 1.5 ppm at the beginning of the cropping sequence.